The black flies (Diptera: Simuliidae) of Vietnam - Takaoka, Hiroyuki; Sofian-Azirun, Mohd; Ya’cob, Zubaidah; Chen, Chee Dhang; Lau, Koon Weng; Low, van Lun; Pham, Xuan Da; Adler, Peter H. (Zootaxa, 2017)
The biodiversity of black flies (Diptera: Simuliidae), which are biting insects of medical and veterinary importance, is strikingly high in Southeast Asian countries, such as Indonesia, Malaysia, Philippines and Thailand. In 2013, we began to explore the fauna of black flies in Vietnam, which has so far been poorly studied. In this monograph, the wealth of the biodiversity of black flies in Vietnam is also confirmed on the basis of the results of our recent investigations, though limited to five provinces in the country. Morphotaxonomic studies of black flies obtained from Sapa, Lao Cai Province, northern Vietnam, in 2014 and Nghe An Province, northern Vietnam, in 2015, and reexaminations of black flies collected from Tam Dao, Vinh Phuc Province, northern Vietnam, in 2013, Thua Thien Hue Province, central Vietnam, in 2014, and Lam Dong Province, southern Vietnam, in 2014, were conducted. A total of 22 species are described as new, including one in the newly recorded subgenus Montisimulium Rubtsov, and three species are recognized as new records from Vietnam. This investigation brings the number of species of black flies known in Vietnam to 70, all of which are assigned to the genus Simulium Latreille, and are placed in four subgenera (25 in Gomphostilbia Enderlein, one in Montisimulium, seven in Nevermannia Enderlein, and 37 in Simulium Latreille s. str.). The numbers of species-groups recognized include seven in Gomphostilbia, three in Nevermannia and nine in Simulium, indicating a high diversity of putative phylogenetic lineages. New species include S. (G.) sanchayense sp. nov. (= the species formerly regarded as S. (G.) brinchangense Takaoka, Sofian-Azirun & Hashim), S. (S.) lowi sp. nov. (= the species formerly regarded as S. (S.) brevipar Takaoka & Davies), S. (S.) fuscicoxae sp. nov. [= the species formerly regarded as S. (S.) rufibasis Brunetti (in part)], S. (S.) suoivangense sp. nov. [= morphoform ‘b’ of the S. (S.) tani Takaoka & Davies (complex)]. Newly recorded species are S. (G.) parahiyangum Takaoka & Sigit, S. (N.) maeaiense Takaoka & Srisuka, and S. (S.) doipuiense Takaoka & Choochote (complex) [= the species formerly regarded as S. (S.) rufibasis Brunetti (in part)]. The substitute name, S. (S.) huense, is given for the species that was described under the name of S. (S.) cavum from southern Vietnam. A redescription of the female, male, pupa and larva of S. (G.) asakoae Takaoka & Davies is presented, and the female and larva of S. (G.) hongthaii Takaoka, Sofian-Azirun & Ya’cob are described for the first time. Keys to 10 subgenera in the Oriental Region and all 70 species recorded from Vietnam are provided for females, males, pupae and mature larvae. As investigations extend nationwide in all the provinces in Vietnam, more new species and records are expected to be discovered. It is hoped that this monograph will be useful as a baseline taxonomic reference for future studies of black flies in Vietnam and neighbouring countries.